Konversi Agama - Nur Aulia Fitri (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Religion is very important in Indonesia. Almost all Indonesian people have one way of life, namely the religion they adhere to. There are many religions in Indonesia. Although there are only six recognized religions in Indonesia, namely Islam, Christianity, Protestantism, Hinduism, Buddhism and Confucianism. From this diversity of religions, Indonesian society can be said to be a multicultural society. In Indonesia, people are free to choose a religion that they believe in and that is the right of every citizen. This is also supported in the Universal Declaration of Human Rights. In the end, freedom of religion creates many situations of religious conversion in society. The phenomenon of religious conversion in Indonesia has become commonplace, especially since freedom of religion is guaranteed by law. Religious conversion is a phenomenon that often occurs in interfaith couples in uniting their love to the marriage level. One of the impacts that the perpetrators of religious conversion receive from their actions is experiencing gaps or conflicts with their families of origin which in turn affects the relationship with their partner to become disharmonious. In building a harmonious relationship between partners, they must have the nature of mutual understanding and understand the differences between fellow families. Keywords: religion; religious conversion; process of religious conversion.